THE BASIC CONDITIONS FOR DEVELOPMENT OF MATHEMATICAL SPEECH OF STUDENTS IN THE PROCESS OF BILINGUAL EDUCATION - L. L. Salekhova; N. I. Spiridonova (Russian State Vocational Pedagogical University, 2018)
Introduction. Many teachers and methodologists note that children, especially at the first step of education and at the initial stage of the secondary school, often can not fully understand and precisely express in oral and written forms their thought and information which is presented in mathematical texts. In the process of mathematical education of the bilingual pupils of younger and middle school age studying at schools with teaching national (native for them) and Russian (state) languages, this task becomes complicated even more since children do not possess the so-called control mechanisms to switch from one language into another as well as speech and thought processes are generally operated in the native language.The aim of the present publication is to determine the main conditions for the development of the mathematical speech of the bilingual students.Methodology and research methods. The research was carried out with a support on activity and personality oriented approaches in education. The research methods involved: analysis of psycho-pedagogical and educational-methodical literature; observation of the process of education in Mathematics of the bilingual students; questioning of school students and teachers; conversations with the respondents.Results and scientific novelty. The close interconnection of the processes of the development of mathematical speech and mathematical thinking is demonstrated, wherein a connective component of speech and thinking is perception of the meaning of the educational material by pupils. The stages of formation of the mathematical speech of pupils and non-language abilities which have to be acquired in the course of bilingual education in mathematics are described. The set of basic communicative qualities for assessment of formation level of the mathematical speech of pupils is designated.On the example of the activities of national schools of the Sakha (Yakutia) Republic, the problems existing today in bilingual education are revealed. One of them is the fact that at primary school and when moving to secondary school the features of bilingual students' speech and thought activities, which are usually formed and operated in the native language, are not considered. However, when choosing educational means, the teachers have to give preference to the Russianlanguage sources and to pay considerable attention to the Russian language itself, as the Russian becomes the main language at the secondary school. Besides, the texts of All-Russian Test Works (an obligatory monitoring activity for graduates of primary school) are not translated into the native language of pupils.Practice has shown, however, that early education in a non-native language has negative effect on school students' development of thinking and mathematical speech that lead to formal knowledge. In contrast, a child whose mathematical speech is formed in the native language at primary school, then, at the secondary school, easily switches into the Russian-language education and successfully improves own mathematical speech based on the acquired experience and complete system of mathematical concepts. Therefore, the most part of the teachers interviewed during the conversations and questioning are convinced that younger school students need to be taught in the language which they speak and think. Smooth transition into the Russian-language education should be introduced in the 5-6th grades; at the same time, continuity between education stages has to be maintained.Practical significance. The materials of the research and the authors' recommendations on designing the conditions for successful development of mathematical speech and thinking of school students studying in the bilingual national-Russian environment can be useful to experts who are engaged in the development of techniques and methods for national comprehensive schools of Russia.